Psychiatric aspects of temporal lobe epilepsy before and after anterior temporal lobectomy - Glosser, G. (BMJ Group, 2000)
OBJECTIVES—Psychopathology has been reported to be prevalent both before and after surgical treatment for medically intractable temporal lobe epilepsy. Individual patients were evaluated prospectively to assess the effect of anterior temporal lobectomy (ATL) on prevalence and severity of psychiatric disease. METHODS—Psychiatric status was assessed in a consecutive series of epilepsy patients before and 6 months after ATL using a structured psychiatric interview, psychiatric rating scales, and self report mood measures. RESULTS—A DSM-III-R axis I diagnosis was present in 65% of patients before and after surgery. The most common diagnoses were depression, anxiety, and organic mood/personality disorders. There was a trend for major psychiatric diagnoses to be more common in patients with right compared to left temporal lobe seizure focus, both before and after surgery. The apparent stability in the overall rate of psychiatric dysfunction concealed onset of new psychiatric problems in 31% of patients in the months shortly after surgery, and resolution of psychiatric diagnoses in 15% of patients. In the group as a whole, the severity of psychiatric symptoms was lower at 6 months postsurgery than before temporal lobectomy. CONCLUSIONS—The overall prevalence of psychiatric dysfunction was comparably high before and after ATL, but individual changes in psychiatric status and changes in severity of symptoms occurred in many patients in the 6 months after surgery.